Pengaruh Nilai Tambah Ekonomis, Earning Per Share dan Price Earning Ratio terhadap Pengembalian Saham - TRI SUSETYO, ANANTA TRI (Jurnal Ilmu Manajemen (JIM), 2013)
Performance of the company can determine how much return to be provided to investors. This study aimed to analyze the effect of Economic Value Added and profitability ratios include Earning Per Share and Price Earning Ratio to stock return. The research sample used in this study is a food and beverage company listed on the Indonesia Stock Exchange (BEI) with the observation period 2007-2010 by using purposive sampling. This study uses multiple regression analysis. The results showed that the variables together Economic Value Added, Earning Per Share, Price Earning Ratio and significant effect on stock returns. As for the individual testing Economic Value Added has no effect on stock returns. Earning Per Share positive effect on stock returns. Price Earning Ratio terhadapat high positive stock return. The three independent variables can only influence the independent variable of 20.1%, while 79.9% are influenced other variables. Keywords: economic value added, earning per share, price earning ratio and stock return.